Envisaging the job satisfaction and turnover intention among the young workforce: Evidence from an emerging economy - Al Mamun, Abdullah; Chen, Xuelin; Wan Hussain, Wan Mohd Hirwani; Jingzu, Gao; Yang, Qing; Al-Shami, Samer Ali Hussein (Public Library of Science CODEN, 2023)
As the economy evolves and markets change after Covid-19, demand and competition in the labor market increase in China, and employees become increasingly concerned about their career opportunities, pay, and organizational commitment. This category of factors is often considered a key predictor of turnover intentions and job satisfaction, and it is important that companies and management have a good understanding of the factors that contribute to job satisfaction and turnover intentions. The purpose of this study was to investigate the factors that influence employees’ job satisfaction and turnover intention and to examine the moderating role of employees’ job autonomy. This cross-sectional study aimed to quantitatively assess the influence of perceived career development opportunity, perceived pay for performance, and affective organisational commitment on job satisfaction and turnover intention, as well as the moderating effect of job autonomy. An online survey, which involved 532 young workforce in China, was conducted. All data were subjected to partial least squares-structural equation modelling (PLS-SEM). The obtained results demonstrated the direct influence of perceived career development, perceived pay for performance, and affective organisational commitment on turnover intention. These three constructs were also found to have indirect influence on turnover intention through job satisfaction. Meanwhile, the moderating effect of job autonomy on the hypothesised relationships was not statistically significant. This study presented significant theoretical contributions on turnover intention in relation to the unique attributes of young workforce. The obtained findings may also benefit managers in their efforts of understanding the turnover intention of the workforce and promoting empowerment practices.